Tips to Improve Work Performance - Pranata, Wim; B, Mesra (PT. Multidisciplinary Press Indonesia, 2024)
The type of research used in this research is quantitative research. The research location is at the Bank Indonesia Representative Office, North Sumatra Province, precisely on Jalan City Hall No. 4, Medan City. The research population used is all employees at the Bank Indonesia Representative Office, North Sumatra Province. as many as 70 employees. The sample to be used is the entire population in the Bank Indonesia Representative Office, North Sumatra Province, totaling 70 employees. The data collection technique used is a questionnaire, the research calculating tool is the Smart PLS version 3 application. The results of this research are as follows. as follows: Competence has a positive and significant effect on Job Performance with a value of 0.384 and a significant 0.000. Work Conflict has a negative and significant effect on Competency with a value of -0.289 and a significant 0.004. Work conflict has a negative and significant effect on work performance with a value of -0.278 and a significant value of 0.009. HR quality has a positive and significant effect on competency with a value of 0.622 and a significant value of 0.000. Human resource quality has a positive and significant effect on work performance with a value of 0.306 and a significant value of 0.005. Role Conflict has a negative and significant effect on Job Performance through Competency with a value of -0.111 and a significant value of 0.016. HR quality has a positive and significant effect on work performance through competency with a value of 0.239 and a significant value of 0.000.